2020
DOI: 10.1051/bioconf/20202700093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic fertilizers on buckwheat yield

Abstract: The paper discusses the effect of pre-sowing treatment of buckwheat with organic fertilizers on its structural indicators, yield and susceptibility to root rot. It was found that fertilizing has a positive effect on growth, development and yield of buckwheat in comparison with the control. Potassium humate was revealed to be particularly effective and showed the yield range from 3.2 t/ha in Chishminskaya and Barynya varieties and to 4.0 t/ha in Devyatka variety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This result was expected because the plant received additional nutrients for growth from the used fertiliser. Many authors (Katar et al, 2022;Sazhina et al, 2020) have found a similar influence of fertilisers on the development of buckwheat. However, some authors also found that fertilisation can reduce yield.…”
Section: Resultsmentioning
confidence: 73%
“…This result was expected because the plant received additional nutrients for growth from the used fertiliser. Many authors (Katar et al, 2022;Sazhina et al, 2020) have found a similar influence of fertilisers on the development of buckwheat. However, some authors also found that fertilisation can reduce yield.…”
Section: Resultsmentioning
confidence: 73%
“…The efficient management of fertilizers should be carried out not only to avoid nutrient leaching but also because providing an extra amount of nitrogen does not result in an increase in crops' seed performance and quality [40]. Although, when BW was fertilized, height was unaffected by the fertilizer type used (Figure 1), the values were in the range of the height reported in the literature [20], and some not significant tendencies to taller plants under MSW treatments were observed. A similar effect was observed for the crop yield.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, natural fertilization with manure obtained a positive response of N and nutrient content on BW and the chemical properties of the soil [7]. Additionally, the complex mixture of organic mineral fertilizers exhibited a positive influence on some BW varieties, increasing crop productivity [20].…”
Section: Introductionmentioning
confidence: 90%